2016
DOI: 10.1186/s13287-016-0312-5
|View full text |Cite
|
Sign up to set email alerts
|

How electromagnetic fields can influence adult stem cells: positive and negative impacts

Abstract: The electromagnetic field (EMF) has a great impact on our body. It has been successfully used in physiotherapy for the treatment of bone disorders and osteoarthritis, as well as for cartilage regeneration or pain reduction. Recently, EMFs have also been applied in in vitro experiments on cell/stem cell cultures. Stem cells reside in almost all tissues within the human body, where they exhibit various potential. These cells are of great importance because they control homeostasis, regeneration, and healing. Nev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
98
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(100 citation statements)
references
References 47 publications
2
98
0
Order By: Relevance
“…The amplification of the signal to a biological response in past years has been thought to be driven solely by the chemical messengers and receptors, but now, there is evidence that the molecular mechanisms may not be the only factors involved in the biological communication. Chemical messengers are perhaps the particle components modulated by the governing energy fields which underlie the signal transduction [4,5]. Our results highlight the beneficial effects of the ELF-EMF on the immune reactions by the stimulation of the T lymphocytes proliferation and by the regulation of the cytokines and free radicals, biological processes that are necessary in the healing of wounds.…”
Section: Staphylococcus Aureusmentioning
confidence: 80%
“…The amplification of the signal to a biological response in past years has been thought to be driven solely by the chemical messengers and receptors, but now, there is evidence that the molecular mechanisms may not be the only factors involved in the biological communication. Chemical messengers are perhaps the particle components modulated by the governing energy fields which underlie the signal transduction [4,5]. Our results highlight the beneficial effects of the ELF-EMF on the immune reactions by the stimulation of the T lymphocytes proliferation and by the regulation of the cytokines and free radicals, biological processes that are necessary in the healing of wounds.…”
Section: Staphylococcus Aureusmentioning
confidence: 80%
“…Numerous investigations have shown that ELF-EMFs can stimulate the division of stem cells [37][38][39][40][41]. It is well established that exposure to ELF-EMFs results in induction of electric fields and associated currents in tissues, an effect that has been used to promote tissue regeneration [1,42,43].…”
Section: Elf-emfs May Increase the Risk Of Childhood Leukemia By Prommentioning
confidence: 99%
“…This effect has been observed with relatively weak magnetic fields (碌T and mT) [1,44]. Since the division of stem cells is crucial for tissue regeneration, it is not surprising that ELF-EMFs can stimulate the division of stem cells of a variety of tissues [37][38][39][40][41].…”
Section: Elf-emfs May Increase the Risk Of Childhood Leukemia By Prommentioning
confidence: 99%
See 1 more Smart Citation
“…It is also known that HSCs migrate during embryonic development and early childhood; the migration of HSCs allows different sites to participate in hematopoiesis at different moments in life [184,185]. Importantly, numerous investigations have shown that ELF-EMFs can stimulate the division of stem cells and promote tissue regeneration [34,[186][187][188][189][190][191][192]. In addition, cell migration is regulated by physiological electric currents [123,[193][194][195], and ELF-EMFs are known to induce electric currents that can alter cell migration [34,88,191,192,[196][197][198].…”
Section: The Stem Cell Division Theory Of Cancer Provides a New Framementioning
confidence: 99%